Retail buying: better purchasing and inventory control - Fiorito, Susan S. (Henry Stewart Talks, 2013)
Importance of inventory control, Key inventory terminology, Assortment strategies, Other assortment factors, Types of merchandise, Developing better customer relationships, Forecasting inventory needs, Functions of inventory, Inventory management systems, Inventory replenishment systems